HASIL DAN STABILITAS HASIL BIJI KEDELAI GLYCINE MAX (L.) MERR. GALUR HARAPAN DI LAHAN SAWAH - Krisnawati, Ayda; Adie, M Muchlish; Susanto, GWA (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Soybean Glycine max (L.) Merr. varieties with consistently high yield productivity across environments are expected to maintain its production level per area.The objectives of this experiment are to determine the magnitude of G × E interaction and to identify the stability of eight soybean promising lines across locations. Materials consists of eight soybean promising lines (G100H/SHRW-60-38, SHRW-60/G100H-73, SHRW-60/G100H-68, SHRW-60/G100H-66, G100H/SHRW-34, SHRW-60/G100H-5, SHRW-60/G100H-70 and SHRW-60/G 100 H-75) and two check varieties (Kaba and Wilis). The experiments were done in 16 locations (Lampung Tengah, Yogyakarta, Ngawi, Mojokerto, Pasuruan, Malang, Banyuwangi and Lombok Barat, two locations each) during the period of 2009 to 2011. A randomized completely block design with four replicates was used in each location. AMMI analysis (Additive Main Effects and Multiplicative Interaction) was applied to assess the yield stability of those 10 genotypes, and then interpreted in biplot graphic of seed yield for principal components 1 (IPCA1) with the principal component 2 (IPCA2). Seed yield of the 10 soybean lines ranged from 2.63-3.02 t/ha, with 2.81 t/ha in average. The highest yield was obtained by G6 (SHRW-60/G100H-5), whereas G3 (SHRW-60/G100H-68) had the lowest seed yield.The combined analysis showed that lines, locations, and the interaction of lines and locations (G × L) were significantly different for seed yield.The first four Interaction Principal Component Axes (IPCA1, IPCA2, IPCA3 and IPCA4) were significant and accounted for 85.1% of the total GEI. Lines of G100H/SHRW-60-38 (G1), SHRW-60/G100H-66 (G4) and SHRW-60/G100H-5 (G6) were stable and high yielding, and therefore they are proposed to be released as new varieties. The results of this study also suggested that Kaba and Willis were used as specific-check varieties, due to its site-specific adaptability.